2015
DOI: 10.1002/cctc.201501077
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous‐Phase Amination of Biogenic Isohexides by using Ru/C as a Solid Catalyst

Abstract: Figure 4. Reactionkinetics of the amination of isomannide at 170 8Cand 10 bar hydrogen pressure obtained from single-batch experiments. The data point at t = 0hand the connecting linesare added for clarity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…These findings indicate that high H 2 pressure favors not only the RA of 2-HTHP to the target 5-AP product, but also the direct hydrogenation of the highly reactive intermediate of 5-HP and 5-HPIP to 1,5-PD and DPA side-products, respectively. Previous studies in the RA of carbonyl compounds 29 and the direct amination of alcohols 6,31,34 also show that increase of H 2 pressure promoted both the desired and side reactions. Therefore, an appropriate H 2 pressure, i.e., 2 MPa is required for the efficient RA of 2-HTHP to produce 5-AP.…”
Section: ■ Results and Discussionmentioning
confidence: 81%
“…These findings indicate that high H 2 pressure favors not only the RA of 2-HTHP to the target 5-AP product, but also the direct hydrogenation of the highly reactive intermediate of 5-HP and 5-HPIP to 1,5-PD and DPA side-products, respectively. Previous studies in the RA of carbonyl compounds 29 and the direct amination of alcohols 6,31,34 also show that increase of H 2 pressure promoted both the desired and side reactions. Therefore, an appropriate H 2 pressure, i.e., 2 MPa is required for the efficient RA of 2-HTHP to produce 5-AP.…”
Section: ■ Results and Discussionmentioning
confidence: 81%
“…It could be emphasized that Rose et al reported the first mono‐amination of isosorbide using Ru/C in aqueous ammonia under H 2 pressure at 170 °C within 50 to 60 % conversion (GC). Due to a lack of diastereoselectivity, a mixture of the two amino‐alcohols was obtained . More recently, Barta et al also reported the mono‐amination of isosorbide using a supported‐Ni catalyst and aqueous ammonia within 32 to 51 % GC yield but without information concerning the stereochemistry .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was proven that also solid catalysts such as Ru/C can be used in the amination of isohexides . To maintain catalyst activity, a certain hydrogen pressure of at least 5 bar is necessary.…”
Section: Monomers Based On Cellulose Hemicellulose and Ligninmentioning
confidence: 99%